Optimizing Healthcare Service Efficiency Through Lean Healthcare and Root Cause Analysis: Meningkatkan Efisiensi Layanan Kesehatan Melalui Lean Healthcare dan Analisis Penyebab Utama - Difa Nur Pratiwi; Sumiati Sumiati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Healthcare service quality plays a crucial role in ensuring patient satisfaction and operational efficiency. However, primary healthcare centers in Indonesia often experience inefficiencies, particularly related to long waiting times. Specific Background: Puskesmas X recorded the highest outpatient visits with significant delays in the general clinic, indicating potential waste in its service process. Knowledge Gap: Despite numerous studies on lean implementation in hospitals, limited evidence exists regarding its systematic application in community health centers using integrated Lean Healthcare and Root Cause Analysis (RCA). Aims: This study aims to identify dominant waste factors in healthcare services and propose improvement strategies to enhance service efficiency. Results: Using Value Stream Mapping (VSM) and RCA, findings reveal that the total service time decreased from 5626 to 2583 seconds, with value-added activities increasing by 18.6% and non-value-added activities reduced by 27.2%. Novelty: The integration of Lean Healthcare with RCA provides a structured analytical model for identifying, prioritizing, and addressing waste in public health service settings. Implications: The proposed improvements—digital queue systems, process standardization, and staff training—demonstrate significant potential to improve patient flow efficiency and enhance service quality at primary care facilities. Highlights: Identifies dominant waste types and their root causes in healthcare services. Demonstrates efficiency improvement through Lean Healthcare and RCA integration. Proposes practical digital and procedural solutions to reduce waiting time. Keywords: Lean Healthcare, Root Cause Analysis, Waste Reduction, Service Efficiency, Primary Healthcare